2021
DOI: 10.1016/j.apmt.2021.100997
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput compositional mapping of phase transformation kinetics in low-alloy steel

Abstract: Knowledge of phase transformation kinetics is a key point in designing steel grades, in particular modern high-performance grades, highly sought-after in energy and transportation applications.The design space for these grades is highly multi-dimensional given the numerous potential alloying elements. The characterization techniques that are usually relied on to assess transformation kinetics, such as metallography or dilatometry, are highly time consuming, due to their limitation to either a single transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The graded samples Fe-C-X 1 -X 2 were created from homogeneous ternary samples Fe-C-X 1 and Fe-C-X 2 (listed in table 1), where X 1 and X 2 are substitutional elements (Ni, Mo or Cr). The methodology used to fabricate the diffusion couples was already detailed in a previous study [13] and only a summary is given below.…”
Section: The High-throughput Methodologymentioning
confidence: 99%
See 4 more Smart Citations
“…The graded samples Fe-C-X 1 -X 2 were created from homogeneous ternary samples Fe-C-X 1 and Fe-C-X 2 (listed in table 1), where X 1 and X 2 are substitutional elements (Ni, Mo or Cr). The methodology used to fabricate the diffusion couples was already detailed in a previous study [13] and only a summary is given below.…”
Section: The High-throughput Methodologymentioning
confidence: 99%
“…However, it is now well documented that these two models are not suitable to describe ferrite growth kinetics in alloyed steels [9,10,11,12]. Some of the experimental results showed that the measured kinetics can be slower than the predicted ones using PE and LE [9,13]. This additional dissipation of the driving force was explained by two main factors, the intrinsic interface mobility [14,15] and solute drag (SD).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations